1980
DOI: 10.1002/cber.19801130106
|View full text |Cite
|
Sign up to set email alerts
|

Wasserstoffübertragungen, Teil 4. Mechanismus der stereoselektiven Wasserstoffübertragung von 1,2‐Dihydronaphthalin auf Tetracyanethen

Abstract: Die Wasserstoffiibertragung von 1,2-Dihydronaphthalin (1) auf Tetracyanethen (2) verlauft hoch stereoselektiv. Die kinetischen Isotopeneffekte widerlegen aber einen elektrocyclischen Ablauf und beweisen, daR ein ionischer, mehrstufiger Mechanismus vorliegt . Ein sterisch fixiertes Ionenpaar ist Ursache der Stereoselektivitat. Hydrogen Transfer Reactions, Part 4l) Mechanism in the Stereoselective Hydrogen Transfer from 1,2-Dihydronaphthalene to TetracyanoetheneThe hydrogen transfer between 1,2-dihydronaphthaIen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…It is reasonable to suppose that radical dissociation could take place in the benzimidazoles as well as at elevated temperatures. Our results support the contention of Dmitrienko et al 6 that initial attack of sulfenyl chloride on indoles takes place at a carbon rather than nitrogen. Certainly the rearrangements reported here and by Dmitrienko et al require far more stringent conditions than in the reactions of indole salts and sulfenyl chloride described earlier.5 One possible explanation for the sulfenylation at carbon, even under conditions where acyla- tion and alkylation take place at nitrogen, involves the hard and soft acid and base (HSAB) concept.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is reasonable to suppose that radical dissociation could take place in the benzimidazoles as well as at elevated temperatures. Our results support the contention of Dmitrienko et al 6 that initial attack of sulfenyl chloride on indoles takes place at a carbon rather than nitrogen. Certainly the rearrangements reported here and by Dmitrienko et al require far more stringent conditions than in the reactions of indole salts and sulfenyl chloride described earlier.5 One possible explanation for the sulfenylation at carbon, even under conditions where acyla- tion and alkylation take place at nitrogen, involves the hard and soft acid and base (HSAB) concept.…”
Section: Resultssupporting
confidence: 92%
“…While a heterolytic dissociation-recombination mechanism is improbable, a homolytic mechanism involving dissociation of 4 into 2,4dinitrophenylthiyl and benzimidazolyl radicals seemed a very viable possibility. Indeed, this seems the likely mechanism for the rearrangement of S-(arylthio)indolenines into N-(arylthio) indoles reported by Dmitrienko et al 6 This latter rearrangement takes place in low yield, and the product is accompanied by large amounts of diaryl disulfide and indole, suggestive of the formation of free radicals. This mechanism, also, would require first-order kinetics and can be excluded here.…”
Section: Resultsmentioning
confidence: 72%
“…Tetracyanoethene (TCNE) has been described as an oxidant for aromatisation reactions. 23 Furthermore, it has been shown that TCNE does not react with functionalised pentalenes. 24 Although not a perfect comparison, since in that case the pentalenes were functionalised with electron-withdrawing groups, we tested TCNE in the reaction with the dihydro compound 9 (Scheme 6a).…”
Section: Synthesismentioning
confidence: 99%